Cerebral Hemiatrophy: Etiology and Pathology - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Two types of cerebral hemiatrophy are reported from the Institute of Neuropathology at the University of Giessen, Arndtstrafse FRG.